2006
DOI: 10.1175/jam2406.1
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Precipitation Size and Fall Speed Characteristics within Coexisting Rain and Wet Snow

Abstract: Ground-based measurements of particle size and fall speed distributions using a Particle Size and Velocity (PARSIVEL) disdrometer are compared among samples obtained in mixed precipitation (rain and wet snow) and rain in the Oregon Cascade Mountains and in dry snow in the Rocky Mountains of Colorado. Coexisting rain and snow particles are distinguished using a classification method based on their size and fall speed properties. The bimodal distribution of the particles' joint fall speed-size characteristics at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
202
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 240 publications
(209 citation statements)
references
References 36 publications
6
202
1
Order By: Relevance
“…PARSIVEL detects and identifies eight different precipitation types as drizzle, mixed drizzle/rain, rain, mixed rain/snow, snow, snow grains, ice pellets, and hail, according to the WMO, SYNOP, METAR, and NWS weather codes. Yuter et al (2006) confirmed that PARSIVEL can be employed as a weather sensor because of its capability to distinguish between solid and liquid precipitation. Recently, critical evaluations on PARSIVEL measurements were performed by Battaglia et al (2010), Thurai et al (2011).…”
Section: A Parsivel Disdrometer and Datasetmentioning
confidence: 66%
“…PARSIVEL detects and identifies eight different precipitation types as drizzle, mixed drizzle/rain, rain, mixed rain/snow, snow, snow grains, ice pellets, and hail, according to the WMO, SYNOP, METAR, and NWS weather codes. Yuter et al (2006) confirmed that PARSIVEL can be employed as a weather sensor because of its capability to distinguish between solid and liquid precipitation. Recently, critical evaluations on PARSIVEL measurements were performed by Battaglia et al (2010), Thurai et al (2011).…”
Section: A Parsivel Disdrometer and Datasetmentioning
confidence: 66%
“…In a more recent study, Dai (2008) used 3-hourly weather reports and found that the phase transition from snow to rain over land occurred within a wide range of temperatures from 22 to 48C. Moreover, other studies (Yuter et al 2006;Lundquist et al 2008;Jones 2010) have noted that a 18C wetbulb temperatures around 618C were reasonable limits within which to determine mixed phases of snow and rain.…”
Section: A Data Sourcesmentioning
confidence: 97%
“…We find fall velocities on the order of −3 m s −1 between approximately 11:00 and 12:00 UTC, which cannot be attributed to dry snow. Based on the fall velocity, magnitude is characteristic for wet snow or graupel (Yuter et al, 2006). Note that the melting layer is below this mesoscale feature.…”
Section: The Orographic Precipitation Event: Surface and Radar Observmentioning
confidence: 99%